Vitamin D in asthma and future perspectives - Huang H; Porpodis K; Zarogoulidis P; Domvri K; Giouleka P; Papaiwannou A; Primikyri S; Mylonaki E; Spyratos D; Hohenforst-Schmidt W; Kioumis I; Zarogoulidis K (Dove Medical Press, 2013)
Haidong Huang,1 Konstantinos Porpodis,2 Paul Zarogoulidis,2,3 Kalliopi Domvri,2 Paschalina Giouleka,2 Antonis Papaiwannou,2 Stella Primikyri,2 Efi Mylonaki,2 Dionysis Spyratos,2 Wolfgang Hohenforst-Schmidt,4 Ioannis Kioumis,2 Konstantinos Zarogoulidis2 1Department of Respiratory Diseases, Changhai Hospital/First Affiliated Hospital of the Second Military Medical University, Shanghai, People’s Republic of China; 2Pulmonary Department, “G Papanikolaou” General Hospital, Aristotle University of Thessaloniki, Thessaloniki, Greece; 3Department of Interventional Pneumology, Ruhrlandklinik, West German Lung Center, University Hospital, University Duisburg–Essen, Essen, Germany; 4II Medical Clinic, “Coburg” Hospital, University of Würzburg, Coburg, Germany Abstract: Humans have the ability to synthesize vitamin D during the action of ultraviolet (UV) radiation upon the skin. Apart from the regulation of calcium and phosphate metabolism, another critical role for vitamin D in immunity and respiratory health has been revealed, since vitamin D receptors have also been found in other body cells. The term “vitamin D insufficiency” has been used to describe low levels of serum 25-hydroxyvitamin D that may be associated with a wide range of pulmonary diseases, including viral and bacterial respiratory infection, asthma, chronic obstructive pulmonary disease, and cancer. This review focuses on the controversial relationship between vitamin D and asthma. Also, it has been found that different gene polymorphisms of the vitamin D receptor have variable associations with asthma. Other studies investigated the vitamin D receptor signaling pathway in vitro or in experimental animal models and showed either a beneficial or a negative effect of vitamin D in asthma. Furthermore, a range of epidemiological studies has also suggested that vitamin D insufficiency is associated with low lung function. In the future, clinical trials in different asthmatic groups, such as infants, children of school age, and ethnic minorities are needed to establish the role of vitamin D supplementation to prevent and/or treat asthma. Keywords: vitamin D, asthma, immunomodulation, anti-inflammation